Notes on bat movements in a fragmented landscape in the Tehuantepec Isthmus, Mexico - Lavariega, Mario C.; Briones-Salas, Miguel (THERYA, 2016)
Several studies have observed that bat species respond differently to landscape changes and that individuals tend to expand their home range when the habitat is not optimal. Tropical dry forest in the Isthmus of Tehuantepec, Mexico, shows a high habitat loss and fragmentation by anthropogenic causes. However, how bats use this fragmented landscape is unknown. Therefore, the aim of this study was to describe the temporal and spatial movements of bats fitted with radio transmitters in a fragmented region of the Isthmus of Tehuantepec. In July 2011, six bats belonging to three species were captured: an adult female of Artibeus lituratus, a juvenile female of A. jamaicensis, an adult male of Leptonycteris yerbabuenae (Family Phyllostomidae), and three adult females of Pteronotus parnellii (Family Mormoopidae) were fitted with a radio transmitter. Bats were monitored during night (18:00 to 06:00 h) from fixed stations for 17 days. The activity was obtained by quantifying the frequency of bearings in intervals of one hour. Simultaneous bearings were triangulated for locations, which were exported to a vector map where type of land use and vegetation was determined. The home range was calculated using two techniques: minimum convex polygon and fixed Kernel. A total of 75 bearings corresponding to an adult female of A. lituratus (n = 36, 48.0 %), three adults females of P. parnellii (n = 30, 40.0 %), and an adult male of L. yerbabuenae (n = 8; 10.6 %) were obtained. A juvenile female of A. jamaicensis was located on one occasion (1.3 %). Female of A. lituratus showed activity between 19:00 and 23:00 h and between 24:00 and 05:00 h, with a peak between 03:00 y 04:00 h. This bat widely used the area with preference to riparian vegetation. Based on their locations, a home range (Kernel 95 %) of 8,394 hectares and a minimum convex polygon of 2,587 hectares were estimated. The male of L. yerbabuenae showed activity only between 22:00 and 02:00 h and their locations were on agriculture land (n = 2). The observed activity of P. parnellii began at 20:00 h, it was increased to at 22:00 h (one activity peak between 01:00 and 3:00 h) and gradually declined until 06:00 h. The three females of P. parnellii were located in agricultural land (n = 4) and cultivated pasture (n = 1). The home range of A. lituratus observed in the present study is the largest reported for phyllostomid bats, possibly in response to landscape condition. Activity and locations of three females of P. parnellii and a male of L. yerbabuenae suggest that they occasionally use the study area in their way to more productive areas.